chanches of the immune organs under demielinization and remielinization. - Melnik N.O.; Chaikovsky Yu.B. (Морфологія, 2007)
The purpose of work was to study the morphological changes in thymus and spleen at experimental allergic encephalomyelitis (EAE) and after «Rebif» (interferon β-1a) treatment. With this aim the thymus and spleen of adult rats in 21 and 39 days after initiation of EAE were used. After 14th day induction of EAE “Rebif” was injected subcutaneous in doses: 0,55 mcg daily during 4 days, 1,1 mg daily during 3 days, 0,55 mcg each other day during 15 days. The square of correlation of cortex and medullar parts of lobules of thymus, white and red pulpas of spleen was measured, the calculation of cellular composition of thymus and spleen. The researches showed that the destructive and reactive changes develop in the organs of the immune system at EAE which correlate with the changes in the organs of the nervous system. The pathological changes of thymus and spleen after the EAE initiation are related to the demielinization changes in the nervous fibres of organs of the central nervous system. We conclude the influence of the «Rebif» at EAE was immunosuppressive and accelerates reparation processes in thymus and spleen.